Burden of common infectious diseases in children with growth failure from 1990 to 2021: analysis of the Global Burden of Disease Study - Li, Yujie; Xu, Jin; Li, Zhaoqi; Ren, Meng; Jiang, Shanping (Frontiers in Pediatrics, 2025)
BackgroundChild undernutrition is a serious public health problem that is associated with various infectious diseases (diarrheal diseases, malaria, measles, respiratory infections and tuberculosis). However, an assessment of the global burden of common infectious diseases in children with growth failure is still needed.ObjectiveThis study aims to quantify the global burden of common infectious diseases in children with growth failure and to project future trends to 2050 to contribute to public health interventions.MethodsBy analyzing the Global Burden of Disease Study 2021 (GBD 2021), we assessed the correlation and trend of common infectious diseases in malnourished children, stratified by age, country, and territory. In addition, Bayesian age–period–cohort (BAPC) models were used to predict future patterns until 2050.ResultsWe found that undernutrition among children is closely associated with common infectious diseases. The rate of deaths and disability-adjusted life years among children with diarrheal diseases, malaria, and respiratory infections and tuberculosis was negatively correlated with age. The prevalence of measles was highest in 1–2-year-olds. Diarrheal diseases and malaria are prevalent in Nigeria, measles is endemic in Somalia, and respiratory infections and tuberculosis are widespread in Nigeria and India. The BAPC results show that the malaria burden may increase in the future.ConclusionThis study emphasizes the burden of common infectious diseases in children with growth failure and facilitates international aid and WHO decision-making targeting countries and age groups.